Analisis Perbandingan Profitabilitas Kinerja Keuangan PT. Bukit Asam Persero Tbk dengan PT. Dian Swastatika Sentosa Tbk Periode 2011-2021 - Akmal Fikri; Gheifira Fildzah; Shabrina Lia Zulva; Darmawan; Achmad Jufri (IAIN Madura, 2023)
The Energy Sector is one of the industrial sectors that has a significant influence on increasing company production in particular and a country's economic output in general. Economic improvement is always related to energy use, where the global economy that will continue to grow will result in an increase in demand for energy. This study discusses two energy sector companies, namely PT. Bukit Asam Persero Tbk with PT. Dian Swastatika Sentosa Tbk. By comparing the profitability of the performance of the two companies, because the assessment of financial performance is very important for companies, because knowing financial performance can be used as management in making financial decisions. The purpose of this study was to determine financial performance in terms of profitability ratios based on gross profit margin, net profit margin, basic earning power, return on investment, and return on equity. The statement submitted by the author is the financial performance of PT. Bukit Asam Persero Tbk and PT. Dian Swastatika Sentosa Tbk Period 2011-2022. This study uses secondary data with descriptive quantitative analysis method.